Can RNAi‐mediated hsp90α knockdown in combination with 17‐AAG be a therapy for glioma?. Issue 1 (20th June 2013) - Mehta, Adi; Shervington, Amal; Howl, John; Jones, Sarah; Shervington, Leroy
Abstract : Heat shock protein 90 promotes tumor progression and survival and has emerged as a vital therapeutic target. Previously we reported that the combinatorial treatment of 17AAG/sihsp90α significantly downregulated Hsp90α mRNA and protein levels in Glioblastoma Multiforme (GBM). Here we investigated the ability of cell penetrating peptide (Tat48–60 CPP)‐mediated siRNA‐induced hsp90α knockdown as a single agent and in combination with 17‐allylamino‐17‐demethoxygeldanamycin (17‐AAG) to induce tumor growth inhibition in GBM and whether it possessed therapeutic implications. GBM and non‐tumorigenic cells exposed to siRNA and/or 17‐AAG were subsequently assessed by qRT‐PCR, immunofluorescence, FACS analysis, quantitative Akt, LDH leakage and cell viability assays. PAGE was performed for serum stability assessment. A combination of siRNA/17‐AAG treatment significantly induced Hsp90α gene and protein knockdown by 95% and 98%, respectively, concomitant to 84% Akt kinase activity attenuation, induced cell cycle arrest and tumor‐specific cytotoxicity by 88%. Efficient complex formation between CPP and siRNA exhibited improved serum stability of the siRNA with minimal intrinsic toxicity in vitro . The preliminary in vivo results showed that combination therapy induced hsp90α knockdown and attenuated Akt kinase activity in intracranial glioblastoma mouse models. The results imply that RNAi‐mediated hsp90α knockdown increases 17‐AAG treatment efficacy in GBM. In addition, the cytotoxic response observed was the consequence of downregulation of hsp90α gene expression, reduced Akt kinase activity and S‐G2/M cell cycle arrest. These results are novel and highlight the ability of Tat to efficiently deliver siRNA in GBM and suggest that the dual inhibition of Hsp90 has therapeutic potentials. Abstract : 17‐AAG–siRNA dual treatment exhibits significant anti‐cancer activity in GBM. Combination therapy induced Hsp90α gene/protein knockdown causing Akt inactivation. Hsp90α inhibition causes S‐G2/M cell cycle arrest and GBM‐specific cytotoxicity. Efficient siRNA/CPP interaction improves serum stability of siRNA. RNAi‐mediated hsp90α knockdown increases GBM sensitivity to 17‐AAG.